Nonparametric function estimation of the relationship between two repeatedly measured variables - A. Ruckstuhl; A. H. Welsh; Raymond J. Carroll (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 1997)
We describe methods for estimating the regression function nonparametrically and for estimating the variance components in a simple variance component model which is sometimes used for repeated measures data or data with a simple clustered structure. We consider a number of different ways of estimating the regression function. The main results are that the simple pooled estimator which treats the data as independent performs very well asymptotically but that we can construct estimators which perform better asymptotically in some circumstances.
urn:nbn:de:kobv:11-10063679
Keywords: 330; semiparametric estimation; Local linear regression; local quasi-likelihood estimator; smoothing; variance components